Relevance of Governance Value with Disclosure of Key Audit Matters (KAM) as Mediation - Sri Astuti; Pujiono Pujiono; Kusharyanti Kusharyanti; Heri Susanto; Marita Marita; Dhea Arsinta Yuliana (AKRUAL: JURNAL AKUNTANSI, 2025)
Introduction/Main Objectives: This study aims to examine the effectiveness of corporate governance in enhancing financial reporting quality and its subsequent impact on investor decision-making. Specifically, it investigates the role of the audit committee’s expertise and meeting frequency in governance, using Key Audit Matters (KAM) disclosures as a measure of financial reporting quality, while stock prices reflect investor responses. Background Problems: Corporate governance plays a crucial role in ensuring transparency and reliability in financial reporting. However, the extent to which governance mechanisms, such as audit committee characteristics, influence financial reporting quality and investor perceptions remains unclear. Additionally, while KAM disclosures are intended to reduce information asymmetry, their impact on investor decisions may vary depending on how they are interpreted. Novelty: This study introduces KAM as a mediating variable, linking corporate governance to investor decision-making. It also explores the dual effect of KAM disclosures—while they signify strong governance and transparency, they may also signal heightened risks, potentially leading to mixed investor reactions. Research Methods: The study employs Ordinary Least Squares (OLS) regression analysis on a dataset comprising 253 observations from 2022. Governance is measured by the audit committee’s expertise and meeting frequency, financial reporting quality by KAM disclosures, and investor decisions by stock prices. Finding/Results: The results indicate that the audit committee’s expertise significantly influences stock prices, with KAM acting as a competitive moderating variable. A highly skilled audit committee leads to more detailed KAM disclosures, reflecting strong governance. However, increased KAM disclosures may also be perceived by investors as indicators of potential risks, affecting stock prices negatively despite the underlying transparency. Conclusion: While robust corporate governance improves financial reporting quality through thorough KAM disclosures, the market’s interpretation of these disclosures can be complex. Investors may associate higher KAM disclosures with elevated risks, even when they stem from strong governance practices. This highlights the need for clearer communication in audit reporting to align transparency with investor confidence.